THE STATE RESPONSIBILITY ON THE IUU FISHING : THE REFLECTION OF THE 2015 ITLOS ADVISORY OPINION ON IUU FISHING AND ITS RELEVANCE TO INDONESIA - Putri, Siti Noor Malia (Indonesia Law Review, 2018)
Illegal, Unregulated and Unreported (IUU) fishing activities have been widely known as a threat to marine living resources. The International Tribunal for the Law of the Sea (ITLOS) has adopted its advisory opinion on the responsibility and the possible liability of the flag States who committed IUU fishing activities in an area under the jurisdiction of the Sub-Regional Fisheries Commission (SRFC). Other than the Opinion, many international scholars and legal instruments have arisen the same concern, however, the primary source on the Law of the Sea, the United Nations Convention on the Law of the Sea (UNCLOS) is silent in this matter. The issue is very relevant with the current case that encountered by the Indonesian Government with regard to the Chinese-flagged fishing boat, namely Kway Fey 10078, that had been suspected to conduct IUU fishing activities in the Indonesian exclusive economic zone (EEZ). In this particular case, the Chinese coast guard ship assisted the Kway Fey to escape from Indonesian jurisdiction by ramming into Kway Fey 10078. In consequence, the Indonesian Government cannot enforce its jurisdiction upon Kway Fey and the Chinese Government requested Indonesia to release eight Chinese nationals who are detained. This reaction shall question on how international provide legal solutions on how to effectively deal with IUU fishing activities.